Method for determining coordinates road and building cars on earth's surface at a distance basis until three satellites - Mikhail Sergeevich Korytov; Vitaliy Sergeevich Sherbakov; Roman Yur'evich Sukharev (Вестник СибАДИ)
Describes a method for determining the coordinates of points on the surface based on the distance to three satellites. The method for determining the coordinates of the road and construction machinery on the surface of the Earth with the help of global positioning system GLONASS / GPS. The mathematical apparatus of homogeneous coordinates. Used welcome replacement for the original formulation of the solutions of the problem areas of the three equations in Cartesian coordinates to the simplified with additional constraints on the direction of the coordinate axes. The solution simplified the task acts as a stage solving the original problem. Performed computer check of the developed method, which has proved its adequacy and efficiency. The minimum number of GLONASS / GPS satellite using the developed method can be reduced from four to three to known techniques.